Energy subsidies in India: proactive versus reactive change - Sen, A (Oxford Institute for Energy Studies, 2012)
In June 2010, the Indian government deregulated the retail prices of petrol. Shortly afterwards, the ‘administered’ price of gas was raised to double its previous level. The prices of ‘sensitive’ petroleum products – diesel, kerosene and LPG, have also progressively been increased; petrol prices rose by roughly 33 percent between June 2010 and November 2011, while diesel rose by just under 2 percent. Simultaneously, measures also began to be put in place to reform the method of meeting distributional objectives in energy, by way of direct provision or transfer of subsidy amounts to consumers. As energy in India has historically been priced very low, these changes reflect a transition in the energy sector, which is arguably part of a wider movement of the economy, from a system of central planning and quantitative allocation, to one based on market principles.